Sitting height percentiles in 3–17-year-old Indian children: a multicentre study. (3rd April 2019) - Khadilkar, Anuradha; Ekbote, Veena; Kajale, Neha; Chiplonkar, Shashi; Prasad, Hemchand; Agarwal, Sanwar; Singh, Narendra; Patwardhan, Vivek; Lubree, Himangi; Ladkat, Dipali; Mandlik, Rubina; Vispute, Smruti; et al.
Abstract: Background: Sitting height (StH) percentiles are not described for the Indian paediatric population. Aim: To generate multicentre StH percentile values for Indian children. Subjects and methods: A total of 7961 apparently healthy children (3–17 years old, Boys: 4328) randomly selected from 10 schools from six states of India were measured for height (ht), StH and weight during July 2016–October 2017. Results: The StH:Ht ratio was 0.52 (0.02) and was similar between boys and girls ( p  > 0.1). The ratio decreased in boys until the age of 14 years and then slightly increased; the lowest ratio was observed during 13–15 years. In girls, however, the StH:Ht ratio decreased until the age of 9 years and then plateaued until 15 years of age with a slight increase at 16 years; the lowest ratio was observed at the age of 12–13 years. Sitting height percentiles (3rd, 10th, 25th, 50th, 75th, 90th and 97th) were computed using LMS chartmaker. Conclusions: The results indicate that, during the pubertal years, the lower limb growth is more predominant than trunk growth. Further, this study provides smoothened percentile curves for sitting height in Indian children for the first time.